2018
DOI: 10.1002/ecm.1297
|View full text |Cite
|
Sign up to set email alerts
|

Living in a high CO2 world: a global meta‐analysis shows multiple trait‐mediated fish responses to ocean acidification

Abstract: Understanding how marine organisms will be affected by global change is of primary importance to ensure ecosystem functioning and nature contributions to people. This study meets the call for addressing how life‐history traits mediate effects of ocean acidification on fish. We built a database of overall and trait‐mediated responses of teleost fish to future CO2 levels by searching the scientific literature. Using a meta‐analytical approach, we investigated the effects of projected CO2 levels by IPCC for 2050–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 109 publications
(265 reference statements)
3
149
0
2
Order By: Relevance
“…A recent meta‐analyses revealed that the data basis is still too limited to allow for generalizations with regard to ocean acidification effects on growth among fish species (Cattano, Claudet, Domenici, & Milazzo, ). The strong interaction between food supply and CO 2 treatment on growth and development observed in this study highlights that food regime is important in assessing the impacts of ocean acidification on marine fishes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analyses revealed that the data basis is still too limited to allow for generalizations with regard to ocean acidification effects on growth among fish species (Cattano, Claudet, Domenici, & Milazzo, ). The strong interaction between food supply and CO 2 treatment on growth and development observed in this study highlights that food regime is important in assessing the impacts of ocean acidification on marine fishes.…”
Section: Discussionmentioning
confidence: 99%
“…Whole lifecycle effects of elevated CO 2 exposure remain critically understudied in fish [25]. While acclimation to chronic hypercapnia likely has small metabolic costs [86], over longer timescales tradeoffs associated with increased acid/base regulation could compromise other physiological processes [43].…”
Section: Discussionmentioning
confidence: 99%
“…LnRRs evaluate the average proportional change in a trait relative to control treatments, with negative lnRRs indicating negative CO 2 effects. LnRRs have become a common metric for evaluating CO 2 effects in meta-analyses when comparing variable responses across studies [6,25,74]. LnRRs were calculated as: lnRR(T) = ln(T high or extreme CO2 ) − ln(T control CO2 ).…”
Section: Response Traits and Statistical Analysismentioning
confidence: 99%
“…Rising CO2 levels in the ocean are anticipated to affect the physiology and behaviour of marine organisms, with possible impacts on the structure and function of marine ecosystems (Wittmann and Pörtner, 2013;Cattano et al, 2018;Pörtner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%